Faktor-Faktor yang Berhubungan Dengan Kejadian Computer Vision Syndrome - Onesimus Indra, Dennis (Fakultas Ilmu Kesehatan Universitas Gresik, 2022)
In today's digital era, the majority of everyone uses computers, laptops, tablets, smart phones, and various other electronic media that use monitor screens. This media is also known as Visual Display Terminal (VDT). The use of VDT devices can improve work quality and work efficiency, but the use of VDT for a long time can cause health problems, one of which is Computer Vision Syndrome (CVS). The American Optometric Association says that prolonged use of computers, tablets, e-readers, and cell phones can give rise to a group of eye and vision-related symptoms. Symptoms may include tired eyes, headache, double vision, dry eyes, etc. This study aims to find out things related to the incidence of Computer Vision Syndrome (CVS) in students of the Faculty of Medicine, Tarumanagara University so that they can prevent the occurrence of these disorders in the future. This research is cross-sectional analytic. This research was conducted on 192 students of Tarumanagara University using judgmental non-probability sampling technique online. The questionnaire consists of respondent identity, digital media usage data, complaint data, and knowledge data about CVS. The results showed that 155 respondents (80.7%) experienced Computer Vision Syndrome (CVS) and 37 (19.3%) respondents who did not experience Computer Vision Syndrome (CVS). In this study, there was a relationship between gender and the incidence of Computer Vision Syndrome (CVS) (P=0.0001). Meanwhile, the age factor, the use of glasses, the duration of using the Visual Display Terminal, the lighting conditions of the room, and the position of the monitor had no relationship with the incidence of Computer Vision Syndrome (CVS) (p value > 0.05). This research is expected to be a lesson for students to pay more attention to the factors that cause Computer Vision Syndrome (CVS). So that it can reduce the incidence of Computer Vision Syndrome (CVS) in students